# MATH

posted by
**Shay**
.

solve 1-(2/x)=2/(x+2)

Express your answer in simplest radical form.

What is radical form ne how?

1-(2/x)=2/(x+2)

Multiply both sides by x(x+2):

x(x+2) - 2(x+2) = 2x

Note that we cannot allow x to be 0 or minus two because for these values the original equation is not defined. The left hand side is:

x(x+2) - 2(x+2).

Factor out the term (x + 2):

x(x+2) - 2(x+2) = (x-2)(x+2) = x^2 - 4

If you now bring the term 2x from the right hand side to the left you get the equation:

x^2 - 2x - 4 = 0 --->

x = 1 +/- sqrt[5]